Pengaruh Pemasaran Digital dan Customer Review terhadap Minat Beli Konsumen pada Pengguna Aplikasi Shopee di Kota Surabaya - Alfidha Nur Fadhilla; Iswati Iswati; Anis Fitriyasari (Jurnal Simki Economic, 2024)
This study aims to analyze the influence of digital marketing and customer review on consumer buying interest in shopee application users in the Surabaya City. This study uses a quantitative method with a survey approach, where data is collected through an online questionnaire with a total of 140 respondents. Data analysis was carried out using multiple linear regression to determine the influence of independent variables (digital marketing and customer review) on dependent variables (consumer buying interest). The results of the study show that digital marketing has a posistive and significant influence on consumer buying interest. Effective digital marketing strategies, such as the use of social media, online advertising, and promotion through influencers, have proven to be able to increase consumer buying interest. In addition, customer reviews also have a positive and significant influence on consumer buying interest. Positive reviews from other customers give consumers confidence and confidence to make a purchase. Overall, this study emphasizes the importance of digital marketing and customer reviews in increasing consumer buying interest. This finding provides practicial implications for e-commerce businessman, especially shopee, to focus more on innovative digital marketing strategies and good customer review management to increase consumer buying interest in Surabaya.